A Better Way for Ductal Stenting in Patients with Duct-Dependent Pulmonary Flow and Vertical and Tortuous Patent Ductus Arteriosus - Aldudak, Bedri; Akdeniz, Osman; Duyorgan, Onur; Okur, Nilufer Matur; Sivasli, Ozlem Gul; Salik, Fikret (Kare Publ, 2022)
Background: In this study, we aimed to compare the femoral route and the carotid artery route in terms of procedural success of ductal stent implantation in patients with duct-dependent pulmonary blood flow. Methods: The study included 51 patients with duct-dependent pulmonary circulation who underwent ductal stent implantation upon their admission to our clinic between July 2017 and March 2021. In total, 23 patients (group I) underwent ductal stent implantation via the femoral route, while the remaining 28 (group II) underwent the procedure via the carotid artery. The groups were compared in terms of procedural success, time, post-procedural blood pH, lactate levels, and complications. Results: Duct morphology was observed in group 1 as follows: type 1 in 12 patients, type 3 in 8, type 2 in 2, and type 6 in 1 patient. In group 2, 26 patients had type 3, 1 had type 2, and 1 had type 6. The tortuosity index of the patients in group 1 was 1 in 8 patients, 2 in 8 patients, and 3 in 7 patients, while in group 2, it was 1 in 5 patients, 2 in 15 patients, and 3 in 8 patients. The success rate was 69.6% (16/26) in group I and 93.5% (29/31) in group II (P =.030). The cumulative success rate was 88.2% (45/51). The procedural durations were 78.2 +/- 34.1 and 52.1 +/- 22.0 minutes in group I and group II, respectively (P =.002). The mean blood pH values upon the completion of the procedure were 7.26 +/- 0.1 and 7.33 +/- 0.0 in group I and group II, respectively (P =.038). The mean post-procedural lactate levels were 2.8 mmol/L and 2.3 mmol/L in group I and group II, respectively (P =.038). The 2 groups did not show any differences in terms of procedural complications. Conclusion: The carotid artery route can be preferred, especially in vertical and tortuous ductus arteriosus, as it is associated with a high success rate and a short procedural time, as well as a better metabolic condition after the procedure.
Keywords: Duct-depended pulmonary flow; ductal stent implantation; carotid artery access